THE MARXIST CATEGORY CONTENT AND FORM IN LITERARY READING - Pires Franco, Sandra Aparecida; Guizelim Girotto, Cyntia Graziella [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
This study analyzes the work Night in the tavern of Alvares de Azevedo, adaptation published in 2013. The objective of the research was to perceive the relation of the Marxist category content and present form in the work. For the development of the work the methodology of bibliographical research with a critical-dialectic approach was used. The analysis allows to affirm that the relation content and form are indissociable elements in a literary work and favorable for the development of the formation of future readers.
Keywords: Literary work; Content and form; Literary reading; Category marxist